Speech Act Realized By Police Investigator In Interrogation Of Drug Cases At Polres Langkat - Ulistia, Ragiel Ajeng (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2022)
This research deals with speech act which is mainly aimed to investigate the used of speech act by police investigator in interrogation of drug cases at Polres Langkat. This research was applied by descriptive qualitative. The results presented in form of description the findings and the reseacher make accurate explanation about the analysis that found in the research. The researcher found 25 speech acts and 3 types of speech act by police investigator in interrogation of drug cases at Polres Langkat with the duration 16 minutes. The dominant types of speech acts that found in interrogation drug cases by police investigator at Polres Langkat was representatives act, however expressives and commisives act was not found.